THE IMPORTANCE OF LOVE-BASED EDUCATION: An Analysis of the Love Based Curriculum Guidelines in Madrasahs - anas; Akhmad Zaenul Ibad (Assyfa Journal of Islamic Studies, 2026)
Love based education is an educational paradigm that emphasizes compassion, empathy, and harmony in social life, with sincerity throughout the entire learning process. This concept emerged as a response to the reality of educational outcomes in the modern era, which prioritize cognitive factors over affective and spiritual ones.This study employs a literature review method focused on exploring theories and concepts found in various sources related to the concept of love based education from an Islamic educational perspective, as well as its urgency in the development and implementation of madrasah curricula.The objective of this study is to analyze the application of love based learning in love based curriculum guidelines for madrasahs and its implications for the character development of students. This serves as an appropriate strategy for integrating the values of love implemented within the madrasah, family and community environments. This study employed a descriptive qualitative method using document analysis techniques to examine curriculum guidelines and other scholarly works related to the research topic.The results indicate that values of love such as compassion, respect for diversity, empathy and social concern are strongly aligned with the principles of Islamic education. Love based education can create a harmonious learning environment, foster intrinsic motivation, and strengthen the relationship between teachers and students. The integration of values of love into a love based curriculum in madrasahs is essential for realizing a holistic, humanistic and character-building education.